2014
DOI: 10.1186/1471-2180-14-22
|View full text |Cite
|
Sign up to set email alerts
|

The Vibrio cholerae diguanylate cyclase VCA0965 has an AGDEF active site and synthesizes cyclic di-GMP

Abstract: BackgroundDiguanylate cyclases (DGCs) regulate biofilm formation and motility in bacteria by synthesizing the second messenger cyclic di-GMP (c-di-GMP) in response to environmental stimuli. DGC enzymatic activity is believed to be dependent on the presence of a GG(D/E)EF active site motif, however approximately 25% of known DGCs contain a degenerate active site. The Vibrio cholerae protein VCA0965 contains an AGDEF active site and is presumed to be an inactive DGC.ResultsEctopic expression of VCA0965 in V. cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…2C), indicating that protein instability is not responsible for the loss of biofilm formation observed. Previous studies suggested that disruption of a DGC's I-site leads to an inability to form the inactive dimer conformation (22) and that a DGC will still readily adopt its active dimer conformation, leading to c-di-GMP overproduction (8). However, we could not immediately rule out the possibility that the mutant variants of GcbC experienced a loss of the ability to produce c-di-GMP; thus, their catalytic ability is assessed below.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2C), indicating that protein instability is not responsible for the loss of biofilm formation observed. Previous studies suggested that disruption of a DGC's I-site leads to an inability to form the inactive dimer conformation (22) and that a DGC will still readily adopt its active dimer conformation, leading to c-di-GMP overproduction (8). However, we could not immediately rule out the possibility that the mutant variants of GcbC experienced a loss of the ability to produce c-di-GMP; thus, their catalytic ability is assessed below.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial results showing that mutation of the I-site of GcbC reduced biofilm formation was somewhat surprising, given that other studies have found that I-site disruption leads to the overproduction of c-di-GMP and enhanced biofilm formation relative to proteins with functional I-sites (7,8). To analyze the impact of these I-site mutations on c-di-GMP levels, we employed two different assays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent experimentally characterized proteins with a G¡A or G¡S substitution still exhibit significant functionality, demonstrating unexpected flexibility in the GGDEF containing active-site hairpin ( Fig. 2) (17)(18)(19).…”
mentioning
confidence: 99%